The Bacteriology of Acute complicated Appendicitis and its Septic Complication in Sulaimani, Iraq - Faraj, Faruk H.; Amin, Falah H. (Sulaimani Journal for Pure and Applied Sciences, 2003)
Objectives: to determine the role of bacterial infection in acute complicated appendicitis and its septic complications in Sulaimani territory. Design: Prospective study setting: Sulaimani Teaching Hospital (ST4),Sulaimani lraq. Methods : Study of 50 patients (29 men find 21 women, aged 9-60 years with mean, age, of 25.7 years) with acute complicated appendicitis, at the department of surgery, STH, between the 1st of Sept.1995 to 30th of Oct.1996, in order to examine the relevance of culturing peritoneal swabs for the antibiotics given and to determine the bacteriology of the cases ond wound infection . Results: E.Coli was the most frequently isolated aerobes while Bacteria were the most common anaerobes in both aspects of the study . In 90% of these cases, the cultured baceria were completely sensitive to gentamycin and metronidazole (flagyl) and we conclude that these drugs are the most useful agents in the management of complicated cases of acute appendicitis and are cost-effective and no deaths occurred in this study.
Keywords: bacteriology of complicated appendicitis septic complications of complicated appendicitis